Towards a manager's mental model: Conceptual change through business simulation - Palmunen Lauri-Matti; Lainema Timo; Pelto Elina (Elsevier, 2022)
Mental models are relevant in both managerial decision making and management education. Decision-making studies have demonstrated how managers benefit from more accurate mental models by gaining higher-quality heuristics and better performance. However, management education studies assessing mental models as learning outcomes remain rare. This study aims at understanding how students' mental models change during a business simulation course. We designed a pre- and post-simulation concept map assignment that illustrated students' mental models as number of concepts, connections between concepts, and written explanations. The findings of our study demonstrate that students’ mental models changed through two interconnected processes: addition of new knowledge and change of misconceptions in existing knowledge. Based on these results, we composed a model of conceptual change through business simulation gaming. Our study contributes to the research on learning from business simulations and addresses the recent call for more conceptual change research in social sciences by enhancing the conceptual change discussion in the management education literature.